GABAergic activities enhance macrophage inflammatory protein-1α release from microglia (brain macrophages) in postnatal mouse brain - Cheung, Giselle (Blackwell Science Inc, 2009)
Microglial cells (brain macrophages) invade the brain during embryonic and early postnatal development, migrate preferentially along fibre tracts to their final position and transform from an amoeboid to a ramified morphology. Signals by which the invading microglia communicate with other brain cells are largely unknown. Here, we studied amoeboid microglia in postnatal corpus callosum obtained from 6- to 8-day-old mice. These cells accumulated on the surface of acute brain slices. Whole-cell patch-clamp recordings revealed that the specific GABA(A) receptor agonist muscimol triggered a transient increase in conductance typical for inward rectifying potassium channels in microglia. This current increase was not mediated by microglial GABA(A) receptors since microglial cells removed from the slice surface no longer reacted and cultured microglia only responded when a brain slice was placed in their close vicinity. Muscimol triggered a transient increase in extracellular potassium concentration ([K(+)](o)) in brain slices and an experimental elevation of [K(+)](o) mimicked the muscimol response in microglial cells. Moreover, in adult brain slices, muscimol led only to a minute increase in [K(+)](o) and microglial cells failed to respond to muscimol. In turn, an increase in [K(+)](o) stimulated the release of chemokine macrophage inflammatory protein-1α (MIP1-α) from brain slices and from cultures of microglia but not astrocytes. Our observations indicate that invading microglia in early postnatal development sense GABAergic activities indirectly via sensing changes in [K(+)](o) which results in an increase in MIP1-α release.